Smart agriculture management system for rice disease detection and fertilizer - Faiyaz, Md Abrar Hossen; Mohsin, Maliha Binte; Nahreen, Nayeema; Oaishi, Sofia Ahmed (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2022.